Rethinking Print Journal Subscriptions at a Large Research University. Issue 2 (3rd April 2021) - Rodriguez, Michael
Abstract: In 2020–2021, the University of Connecticut (UConn) Library ceased more than 90% of its print journal subscriptions for the general collections. This decision was the outcome of a data-based review and cost-benefit analysis. Staff considered factors such as online availability, number of WorldCat holdings, scan-on-demand and interlibrary lending and borrowing activity, and hidden costs of storage and staff time for processing. Recorded usage proved all but nonexistent, with an annual average use of one per title. Additionally, print journals were inaccessible to patrons because of the closure of library stacks during the COVID-19 pandemic. We did not conduct an extensive qualitative review. UConn Library's decisions broke new ground among U.S. research universities, which have winnowed their print subscriptions over the decades but rarely made a decisive break from print. This article will discuss the project, process, decisions, and data and will share UConn's assessment strategies and criteria for reinstituting subscriptions. At stake was the principle that libraries must use their scarce resources effectively—at any scale.